Association of Serum Galectin-3 Level with Albuminuria and Renal Function in Type 2 Diabetic Iraqi Patients - Najlaa abed jassim; Sanad Baqir Mahammad; Tawfeeq F.R. AL-Auqbi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Galectin-3 is a category of ?- galactoside binding Lectin. It has been involved in renalinflammation and fibrosis. We examined the relationship between galectin-3 level and nephropathy in T2DMpatients with or without microalbuminuria in comparison healthy controls.Methods: Ninety T2DM patients they were graded as (3 groups) depending on (ACR) albumin to creatininevalue: normalbuminuria (ACR < 30 mg / g), micro albuminuria (ACR 30-300 mg / g); and macroalbuminuria(ACR > 300 mg / g). In addition, 30 healthy control subject. The serum galectin-3 was determined by anenzyme-linked immune sorbent assay (ELISA) for 90 T2DM patients and 30 healthy subjects. And alsobiochemical parameters measured included FBG, HbA1c, urea, creatinine, and uric acid.Result: Serum galectin-3 was significantly raised in T2DM patients with macroalbuminuria in comparing tohealthy group and also to other patients groups (p<0.001). Galectin-3 level was positively related with eachof ACR, FBS, HbA1c, urea, creatinine. whilst, eGFR was negatively correlated with galectin-3Conclusion: Galectin-3 level is essentially higher with T2DM at all stages of DN, particularly inmacroalbuminuria patients.